2011
DOI: 10.4187/respcare.00988
|View full text |Cite
|
Sign up to set email alerts
|

Survival From Severe Pandemic H1N1 in Urban and Rural Turkey: A Case Series

Abstract: . RESULTS: During the study period, in our ICU we followed 18 patients (10 female) with H1N1. Their median (and IQR) age was 39 y (24 -52 y), their median (and IQR) Acute Physiology and Chronic Health Evaluation (APACHE II) score was 16 (10 -25), and 7 (39%) of them lived in rural places. All 18 patients had acute lung injury (ALI) or acute respiratory distress syndrome (ARDS). The most common risk factors for severe H1N1 infection were obesity (33%), COPD (16%), and pregnancy (11%). Thirteen patients (72%) ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 24 publications
1
11
1
3
Order By: Relevance
“…However, obesity, pregnancy, and comorbid conditions such as chronic obstructive pulmonary disease (COPD) were shown to increase the severity of the disease in pandemic (H 1 N 1 ) influenza-A pneumonia (3,4). In the current study, the average age of the cases was 47.5±18.6 years and 52.1% had co-morbid diseases.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…However, obesity, pregnancy, and comorbid conditions such as chronic obstructive pulmonary disease (COPD) were shown to increase the severity of the disease in pandemic (H 1 N 1 ) influenza-A pneumonia (3,4). In the current study, the average age of the cases was 47.5±18.6 years and 52.1% had co-morbid diseases.…”
Section: Discussionmentioning
confidence: 58%
“…According to the literature, some patients may have a normal chest radiograph at first presentation, but may develop alveolar opacities and bilateral interstitial infiltrates on chest radiographs in the following days (12,21). It was reported that radiological findings were more often bilateral in patients who underwent mechanical ventilation due to severe respiratory failure (4,21,22). Even where no radiological evidence of disease is initially detected, radiological findings may subsequently emerge and serious respiratory failure may develop over a short period.…”
Section: H1n1mentioning
confidence: 99%
See 1 more Smart Citation
“…İnfluenza ve AdV gibi diğer solunum virusları da mevsimsel epidemiler sırasında nadiren akut bronşiyolit ve hospitalizasyonun önemli sebebi olarak rapor edilmektedir 16 . 25,26 . Çalışma-daki örneklerin toplanma periyodu, influenza A H1N1 pandemisine denk gelmiş olup, bu virus RV ile aynı oranda (%29), RSV'den sonra en sık saptanan ikinci virus olmuştur.…”
Section: Discussionunclassified
“…Diversos autores han explorado la importancia de este aspecto y no han logrado mayoritariamente encontrar una asociación con la gravedad de la evolución del cuadro de influenza o un desenlace fatal 11,13,16,21 . No obstante, una serie española con más de 500 pacientes adultos logró demostrar que el tratamiento antiviral hasta las 72 h del inicio de los síntomas, tuvo un efecto protector sobre ingreso a UCI o muerte (OR 0,32) 22 .…”
Section: Características Clínicas Sistemas De Puntuación Y Laboratoriounclassified